2010
DOI: 10.1097/nna.0b013e3181f37e56
|View full text |Cite
|
Sign up to set email alerts
|

Certification and Education

Abstract: Wound care certification and education significantly affect nursing knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Nurses with a wound care certification had a much higher MDRPI knowledge score than nurses without a wound care certification. This result is consistent with the findings of Zulkowski et al 24 Possible reasons for this are that nurses with a wound care certification have attended more training on pressure injuries, have read books and guidelines related to pressure injuries, and are more active in updating information related to pressure injuries. 21 This result suggests that nursing administrators need to train wound specialist nurses with a wound care certification to perform wound care.…”
Section: Discussionsupporting
confidence: 91%
“…Nurses with a wound care certification had a much higher MDRPI knowledge score than nurses without a wound care certification. This result is consistent with the findings of Zulkowski et al 24 Possible reasons for this are that nurses with a wound care certification have attended more training on pressure injuries, have read books and guidelines related to pressure injuries, and are more active in updating information related to pressure injuries. 21 This result suggests that nursing administrators need to train wound specialist nurses with a wound care certification to perform wound care.…”
Section: Discussionsupporting
confidence: 91%
“…The nursing literature revealed that nurses with dedicated didactic training in wound care have improved rates of wound care knowledge, while years in practice alone do not significantly affect wound care knowledge. 19 Within our resident cohort, more years of practice corresponded to greater wound care knowledge and less improvement from pre-to post-test likely related to the increased exposure to wound care over the course of surgical residency. The COVER curriculum fosters an environment in which higher level of competencies can be trained, paralleling the Accreditation Council for Graduate Medical Education (ACGME) Surgical Milestones.…”
Section: Box 2 Cover Lab Objectivesmentioning
confidence: 81%
“…When researchers used the Pieper Pressure Ulcer Knowledge Tool, a validated exam, to assess the knowledge of certified wound care nurses, staff nurses, and physicians, the wound care nurses performed the best, while the physicians performed the worst. [10][11][12] The implication of these findings, we believe, is that the wound care nurse is the expert on pressure injury prevention and care, and an evidence-based wound care guideline developed by this specialist and implemented by staff nurses may be more reliable than wound care orders placed by physicians. Furthermore, while these studies also suggest that additional education is needed for staff nurses, knowledge does not always translate into practice.…”
Section: Introductionmentioning
confidence: 96%